Patterns of progression on osimertinib in EGFR T790M positive NSCLC: A Swiss cohort study. (April 2019) - Schmid, S.; Klingbiel, D.; Aeppli, S.; Britschgi, C.; Gautschi, O.; Pless, M.; Rothschild, S.; Wannesson, L.; Janthur, W.; Foerbs, D.; Demmer, I.; Jochum, W.; et al.
Highlights: In patients with acquired osimertinib resistance rate of oligo-progression is high. Main sites of PD were lung, bone lymph nodes, liver, pleura and brain. Outcomes of patients with oligo-PD who received local ablative therapy were favorable. Abstract: Introduction: Osimertinib is an EGFR tyrosine kinase inhibitor (TKI) with antitumor activity in non-small cell lung cancer (NSCLC) with EGFR T790 M mutations. The incidence of oligo-progression (PD) on osimertinib is unknown. Methods: We retrospectively analyzed 50 pre-treated EGFR T790M-positive NSCLC patients treated with osimertinib at seven Swiss centers. Oligo-PD was defined as PD in ≤ 5 lesions. Mutational profiling of pre- and post-osimertinib tumor samples was performed. Results: Median age was 62 years (37–89), 64% were females, 86% had a PS ≤ 1, 54%/13% were never/current smokers. Median follow-up was 15.3 (IQR: 8.6–21.6) months. Overall response rate was 80%, median progression-free survival 12.1 months (95% CI 8.3–18.3), median overall survival 28 months (95% CI 20.2-not reached [NR]) and median treatment duration 18.8 months (95%CI 16-8-NR). PD occurred in 36 patients (72%). 73% had oligo-PD. Median osimertinib treatment duration in patients with oligo-PD was 19.6 vs. 7 months if systemic PD (p = 0.007). The number of progressive lesions in patients with oligo-PD was 1 (27%), 2 (35%) and 3–5 (39%). Sites of PD included lungs (56%), bones (44%), and brain (17%). Sixteen patients with oligo-PD continued treatment with osimertinib for a median of 6.7 months beyond PD. Thirteen received local ablative treatment (LAT). In pre- and post-PD tumor tissue multiple molecular alterations were detected. Conclusion: In patients with acquired resistance to osimertinib, we observed a high rate (73%) of oligo-PD. Outcomes of patients receiving LAT were favorable, supporting the concept of osimertinib treatment beyond progression in combination with LAT of progressing lesions.